(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
An important task of modern ecology is the modeling of the spatial distribution of organisms. Of particular relevance is the modeling of the distribution of rare species in protected natural areas. The paper discusses the main stages and presents the results of modeling the habitat suitability of the Central Forest State Nature Biosphere Reserve (Russia, Tver region) for the red vole. This species is a rare and relict for the center of the Caspian-Baltic watershed. In the modelling the maximum entropy method (MaxEnt) was used. The basis for building the model was the field sampling of the authors, performed in July-August 2010-2014. Each year, trapping were carried out at 745 sampling points each of which has geographical referencing in the WGS 84. A total of 12238 trap-days were worked out and 141 red vole individuals were caught. In the process of modeling, the contribution to the species distribution of certain integral characteristics of habitats (relief, vegetation type and three vegetation spectral indices) was determined. A map model of habitat suitability for the red vole on the territory of the Reserve was built, which allowed to describe the spatial structure of the population groups of the species. The total areas of the most favorable sites for the habitat of the red vole on the reserve's territory were calculated.